The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0125415
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterisation of Farnesyl Pyrophosphate Synthase from Tripterygium wilfordii

Abstract: Farnesylpyrophosphate synthase (FPS) catalyzes the biosynthesis of farnesyl pyrophosphate (FPP), which is an important precursor of sesquiterpenoids such as artemisinin and wilfordine. In the present study, we report the molecular cloning and characterization of two full-length cDNAs encoding FPSs from Tripterygium wilfordii (TwFPSs). TwFPSs maintained their capability to synthesise FPP in vitro when purified as recombinant proteins from E. coli. Consistent with the endogenous role of FPS in FPP biosynthesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Farnesyl diphosphate (FPP) is the precursor of sesquiterpenoids [ 36 , 37 ]. We identified the key enzyme gene farnesyl diphosphate synthase ( FPPS ; 2.5.1.1) in our library and found that it was significantly up-regulated (unigene16392) in male compared with female beetles, while the gene for isopentenyl-diphosphate delta-isomerase ( IDI ; 5.3.3.2), another important enzyme in terpenoid biosynthesis, was also significantly up-regulated (CL3032.…”
Section: Resultsmentioning
confidence: 99%
“…Farnesyl diphosphate (FPP) is the precursor of sesquiterpenoids [ 36 , 37 ]. We identified the key enzyme gene farnesyl diphosphate synthase ( FPPS ; 2.5.1.1) in our library and found that it was significantly up-regulated (unigene16392) in male compared with female beetles, while the gene for isopentenyl-diphosphate delta-isomerase ( IDI ; 5.3.3.2), another important enzyme in terpenoid biosynthesis, was also significantly up-regulated (CL3032.…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids constitute a large and structurally diverse group of chemicals, playing diverse functional roles in plants as hormones, electron carriers and structural component of membranes [ 48 ]. Farnesyl pyrophosphate synthase (FPS) not only played a vital role in terpenoid metabolism, but also functioned as a key regulatory enzyme to control the sterol biosynthetic pathway [ 49 ]. In our study, FPS as key regulators was significantly accumulated and involved in Terpenoid backbone biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, synthetic biology has been designed, regulated and optimized on different levels to produce new drugs, biofuels, and target products to maximize production ( Gechev et al, 2014 ). In recent years, terpenoid biosynthetic pathway analysis has been the most important part of the research in T. wilfordii ( Li et al, 2009 ; Wu et al, 2012 ; Liu et al, 2014 ; Zhang et al, 2015 ; Zhao et al, 2015 ). Our ongoing studies were focus on identifying preciously uncharacterized related genes in terpenoids metabolism of T. wilfordii .…”
Section: Introductionmentioning
confidence: 99%